Christianity, latinity, and culture : two studies on Lorenzo Valla - Camporeale, Salvatore I.; Baker, Patrick, 1976-; Celenza, Christopher S., 1967-; Valla, Lorenzo, 1407-1457.; Valla, Lorenzo, 1407-1457.; E.J. Brill (Firm) (Boston : Brill, 2013)
This book presents, for the first time in English, two studies by Salvatore I. Camporeale (1928-2002) on the fifteenth-century thinker Lorenzo Valla. Camporeale's work offers new perspectives on Valla, in terms of both content and method.
2.9 The Reduction of Philosophy to Rhetoric and Valla's Quintilianism2.10 The Linguistic-Semantic Critique of Scholasticism and the Interrelation between Greek and Latin; 2.11 Peroration and Closing of the Encomium; 3.1 Philosophy/Theology; 3.2 Dialectic/Rhetoric; 4.1 The proemium to Book IV of the Elegantiae; 4.2 The Letter to Eustochium and Jerome's Dream; 4.3 The Mechanical Arts, the Liberal Arts, and the Christian Religion; 4.4 The Opposition between Philosophical Theology and Rhetorical Theology, and the Critical Reduction of theVulgate to the Greek Truth (veritas graeca).
Includes bibliographical references and index.
Print version record.
Keywords: Valla, Lorenzo, -- 1407-1457.; Constitutum Constantini; Valla, Lorenzo, -- 1407-1457.; Thomas, -- Aquinas, Saint, -- 1225?-1274.; Popes -- Temporal power -- Early works to 1800.; Christianity; Latinity; Religion; RELIGION -- Christian Life -- General; Electronic books; Electronic books